PENAMBAHAN CONTRACT RELAX STRETCHING OTOT PAHA DAN SLUMP STRETCH SETELAH LATIHAN KNEE TUCK JUMP EFEKTIF DALAM MENINGKATKAN DAYA LEDAK OTOT TUNGKAI PADA PEMAIN SEPAK BOLA FISIOTERAPI FK UNUD - Anak Agung Gede Eka Septian Utama; I Made Niko Winaya; I Made Krisna Dinata,; I Wayan Sugiritama (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACT Leg muscle explosive power is the power of maximum leg muscle contractions in a short duration of time. Knee tuck jump exercise is an exercise to increase the explosive power of leg muscle, but it still has its weaknesses because the results are less than optimal. In theory, the addition of contract relax-stretching of the thigh muscles and slump stretch after knee tuck jump exercise is effective in improving leg muscle explosive power. Digital vertical jump test was used to measure vertical jump. Statistical analysis used parametric tests. Group I had average increase of vertical jump by 5.32 cm, p = 0.000 and Group II at 2.10 cm, p = 0.000. Conclusions: The addition of contract relax-stretching of the thigh muscles and slump stretch after knee tuck jump exercise was effective in improving leg muscle explosive power in Physiotherapy FK UNUD football players. Keywords: Explosive power of leg muscle, knee tuck jump, contract-relax stretching, slump stretch, digital vertical jump test